Kesiapan Penyusunan Laporan Keuangan Berbasis Standar Akuntansi Keuangan Entitas Mikro, Kecil, Dan Menengah (Studi Kasus UMKM Pada Toko Bangunan H. Saunin Pebayuran Bekasi) - Fadia Salsabila; Sihabudin Sihabudin; Trias Arimurti (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The preparation of financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) is a crucial factor for MSMEs in managing their finances transparently, accountably, and sustainably. Although this standard is simpler compared to other accounting standards, many MSMEs still face difficulties in its implementation. This study aims to evaluate the readiness of MSMEs in implementing SAK EMKM using a case study on Toko Bangunan H. Saunin. The research method employed is in-depth interviews to identify the main challenges in applying this accounting standard. The results indicate that Toko Bangunan H. Saunin is not yet fully prepared to implement SAK EMKM. The primary obstacles include a lack of accounting knowledge, manual financial record-keeping, limited human resources, and low awareness of the importance of standardized financial reporting. The lack of orderly financial reporting has the potential to hinder access to funding and strategic business decision-making. Therefore, education, socialization, and assistance from various stakeholders are necessary to help MSMEs understand and adopt SAK EMKM effectively. With the proper implementation of accounting standards, MSMEs are expected to enhance financial transparency and accountability, thereby supporting more sustainable business growth.